PENGARUH PRODUCT QUALITY DAN PRICE TERHADAP CONSUMER BUYING INTEREST (Studi Kasus Pada Konsumen Kulit Kayu Lantung Toko Fajri Craft) - Indriani, Reni; Dinna Ihza Mahawati (Universitas Muhammadiyah Bengkulu, 2024)
This studyto determine whete the Product Quality variable and the Price variable have an influence on Consumer Buying Interest. Thia atudy used a quantitative method with an assosiative approach. The population in this study were consumers of lantung wood products from Fajri Craft Store, with a sample size of 96 people. The result of this study showed that product quality and prece have a significant influence on Consumer Buying Interest. Based on the calculation using the coefficient of determination, it was found that the corellation coefficient value was 0.776, indicating a direct correlation between the product quality and price variables with Consumer Buying Interest.